Selective Liquid-Liquid Extraction of Molybdenum (Vi) and Rhenium (Vii) from a Synthetic Pregnant Leach Solution: Comparison Between Extractants and Diluents - Romero-Figueroa, J; Quijada-Maldonado, E; Merlet-Venturelli, G; Cabezas-Cornejo, R (Elsevier Ltd, 2020)
A study on the selective solvent extraction (SX) of Molybdenum (Mo) and Rhenium (Re) from a synthetic pregnant leach solution (PLS) has been carried out using two diluents: kerosene and the ionic liquid (IL) 1-octyl-3-methylimidazolium bis(trifluoromethylsufonyl)imide ([omim][Tf2N]) and two extractants: di(ethylhexyl)phosphoric acid (D2EHPA) and the IL trioctylmethylammonium bis(2-ethylhexyl) phosphinate [TOMA][D2EHP]. It can be concluded that the D2EHPA extractant in kerosene achieved selective Mo-Re extractions, times was achieved when replacing kerosene with [omim][Tf2N], but this time with low extraction percentages. This work shows how ionic liquids, as extractants or diluents, can improve the selective separations in industrial metal extractions. © 2019 Elsevier Ltd